Penerapan Metode Talaqqi Berbantuan Teknologi dan Media Pembelajaran dalam Pembelajaran Al-Qur’an di SMA Islam Terpadu - Zamsiswaya, Zamsiswaya; Risnawati, Risnawati; Armizi, Armizi (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study explores the delivery of Al-Qur'an learning, focusing on using the talaqqi method for Senior High School (SMA) students. Although the talaqqi method is considered traditional, its approach can be adapted to current conditions and technological developments through an integrative strategy that combines both conventional and progressive aspects. This study employs a descriptive qualitative research method at the Darul Rahman Integrated Islamic Senior High School (SMAIT) in Tempuling District, Indragiri Hilir Regency, Riau. Data were collected through interviews with school principals, Al-Qur'an teachers, and Islamic Religious Education (PAI) teachers and through observations. They were analyzed using an interactive analysis model. The results indicate that the process of Al-Qur'an learning using the talaqqi method is conducted by adapting cooperative learning, taking place collaboratively with holistic cooperation, namely partnerships between schools and the community. Second, the learning process incorporates various types of technology and learning media in an integrated manner, combining conventional and digital aspects to accommodate diverse student learning styles. In conclusion, the talaqqi method can be effectively adapted to contemporary educational contexts through cooperative learning and technology integration. This study implies that schools should foster stronger partnerships with parents and the community and develop teacher competencies in using conventional and digital learning media to enhance students' learning experiences.